1998
DOI: 10.1016/s0029-7844(97)00704-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study of the effects of 17Beta-estradiol-dydrogesterone on plasma homocysteine in postmenopausal women

Abstract: Plasma fasting homocysteine concentrations are lowered by E2-dydrogesterone therapy in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(47 citation statements)
references
References 21 publications
3
42
1
1
Order By: Relevance
“…It has been fairly well established that plasma H(e) concentration can be reduced by up to 20% in postmenopausal women who use exogenous estrogen. 34 This could be yet another factor that, in addition to MTHFR genotype and diet, contributes to interindividual variation in plasma H(e) concentration in the present study and in others.…”
Section: Discussionsupporting
confidence: 54%
“…It has been fairly well established that plasma H(e) concentration can be reduced by up to 20% in postmenopausal women who use exogenous estrogen. 34 This could be yet another factor that, in addition to MTHFR genotype and diet, contributes to interindividual variation in plasma H(e) concentration in the present study and in others.…”
Section: Discussionsupporting
confidence: 54%
“…Intact females (n=257) had a mean plasma Hcy concentration of 9.4 ± 0.6 μmol/l (first quartile-median-third quartile 8.5-11.9-16.1 μmol/l, and min-max 2.4-89.5 μmol/l). It has been reported that plasma Hcy concentration tends to increase after menopause in humans, and treatment with 17 β-estradiol-dydrogesterone decreases plasma Hcy concentrations in postmenopausal women (Mijatovic et al, 1998). Trisolini et al, (2008) also reported that the plasma Hcy concentrations were significantly elevated in spayed canines (Trisolini et al, 2008).…”
Section: Sex and Homocysteine Concentrationmentioning
confidence: 98%
“…Men are more commonly affected by HHcy than women because Hcy metabolism is linked to estradiol. Plasma Hcy concentrations also increase with age (Mijatovic et al, 1998). It has been reported that HHcy is related to diseases such as coronary heart disease (Cacciapuoti 2011;Frosst et al, 1995;Humphrey et al, 2008), kidney disease (Friedman et al, 2001), Alzheimer's disease (Moustafa et al, 2012), and rheumatoid arthritis (Roubenoff et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…In a recent randomized, double-blind, controlled study, a significant 13% reduction in fasting tHcy was obtained by treatment with [38] . This confirms findings of previous, uncontrolled studies.…”
Section: Hormones and Thcymentioning
confidence: 99%